Kurikulum Bagi Anak Berkebutuhan Khusus (Spectrum Autism) di SLB kepahiang - Hasanah, Miftah; Andani , Fidhia (JPT : Jurnal Pendidikan Tematik, 2023)
This study aims to determine the school curriculum and shadow teachers in the learning process of children with autism spectrum disorder at SLB 01 Kepahiang School. This research is important to do to understand how schools use the K 13 curriculum, the independent curriculum, or KTPS for children with autism spectrum disorder. This research method uses a qualitative method of subject description conducted with the school and also teachers. This research is used to create questions for interviews, observations, curriculum for children with autism spectrum disorder by using unique media and teaching aids in the learning process to make it easier for children with autism spectrum disorder.